2004
DOI: 10.1097/01.phm.0000143436.57173.e1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ethnic Differences in Willingness to Enroll in a Rehabilitation Research Registry

Abstract: Ethnicity was not found to be a predictor of willingness to enroll in a study registry. A greater belief of gain and less concern over privacy were associated with willingness to enroll, even after controlling for age, education, facility, and ethnic group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…The evidence regarding the relationship between demographic characteristics, health information privacy views and willingness to participate in registries is mixed. One study was identified that examined demographic and clinical variables as well as privacy concerns in predicting willingness to enroll in a cognitive rehabilitation research registry, finding that those who were more concerned about registry privacy were less likely to consent to join the registry, but this study was not conducted with patients after rehabilitation [19]. Similarly, a study that found that non-white women and men were less likely to participate in a family registry for breast cancer research, did not include a post-treatment group [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evidence regarding the relationship between demographic characteristics, health information privacy views and willingness to participate in registries is mixed. One study was identified that examined demographic and clinical variables as well as privacy concerns in predicting willingness to enroll in a cognitive rehabilitation research registry, finding that those who were more concerned about registry privacy were less likely to consent to join the registry, but this study was not conducted with patients after rehabilitation [19]. Similarly, a study that found that non-white women and men were less likely to participate in a family registry for breast cancer research, did not include a post-treatment group [18].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies have been conducted that examined the characteristics of individuals agreeing to participate in patient registries [18][19][20]. More specifically, Phipps et al explored the role of patients' privacy concerns in relation to registry participation [19]. These studies did not include joint replacement recipients.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have previously identified factors that affect subject participation, including physician rapport, physician communication skills, socioeconomic status, expectation of benefit, monetary payments, investigator conflict of interest, and privacy (11)(12)(13)(14)(15). Informed consent for research is an important safeguard to the rights of human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…XXXX has not set aside any funds for compensation for medical expenses or any other compensation for research-related injuries such as lost wages and/or direct or indirect losses. 14 …”
Section: Appendixmentioning
confidence: 97%